Total Plate Count (TPC) Value of Chicken Pentol Snacks Sold in the Kelapa Dua Raya Area, Depok - Diah Ayu Purboningrum; Wulan Fitriani Safari; Enny Khotimah (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Pentol is a street food product made from a mixture of tapioca flour and chicken meat. The public widely favors it due to its palatable taste and relatively affordable price. In Depok City, Kelapa Dua Raya is one of the areas where pentol is commonly sold. However, pentol is at high risk of microbial contamination due to inadequate hygiene during the preparation process and its typical sale in roadside settings. This study aimed to determine the Total Plate Count (TPC) values of Pentol sold in the Kelapa Dua Raya area, Depok. The samples used in this study were pentol obtained from 5 different vendors with duplicate analysis and 8 serial dilutions. Samples were analyzed using the spread plate method on Plate Count Agar (PCA) medium with Buffer Peptone Water (BPW) as the diluent. Colony counts were performed in accordance with the Standar Nasional Indonesia (SNI) 2897:2008, with a countable range of 25–250 colonies per plate. The results showed that the average TPC values were 1.1×10⁷ colonies/g for sample 1, 7.3×10⁶ colonies/g for sample 2, 1.5×10⁵ colonies/g for sample 3, 6.8×10⁷ colonies/g for sample 4, and 7.9×10⁶ colonies/g for sample 5. Four samples, namely samples 1, 2, 4, and 5, exceeded the maximum threshold set by the Food and Drug Supervisory Agency (BPOM) Regulation No. 13 of 2019 at 1×10⁶ colonies/g, while only one sample met the standard